2013
DOI: 10.1093/ajh/hps044
|View full text |Cite
|
Sign up to set email alerts
|

Do the Lactotripeptides Isoleucine-Proline-Proline and Valine-Proline-Proline Reduce Systolic Blood Pressure in European Subjects? A Meta-Analysis of Randomized Controlled Trials

Abstract: BACKGROUNDThe milk-derived peptides isoleucine–proline–proline (IPP) and valine–proline– proline (VPP) have been shown to reduce systolic blood pressure (SBP). This decrease is convincingly shown in subjects of Asian origin, but less consistent results have been obtained in European populations.METHODSA meta-analysis was conducted in accord with the Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) requirements, to assess the effect of IPP and VPP on SBP in Europeans, and to explore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 35 publications
1
68
1
3
Order By: Relevance
“…A metaanalysis of the data from 15 studies showed a small effect on SBP, but no effect on DBP, as mentioned previously (4). Similarly, a recent meta-analysis of 14 studies assessing the BP-lowering effect of the peptides isoleucine-prolineproline and valine-proline-proline exclusively in European subjects has shown a small decrease in SBP and DBP of 1.28 and 0.59 mmHg respectively (21). It cannot be ruled out that the use of BP-lowering medication, ACE/AT2 blockers in our study might have influenced the results; however, we do not find this likely as both dose and type of antihypertensive medication were kept constant during the study period.…”
Section: Discussionsupporting
confidence: 65%
“…A metaanalysis of the data from 15 studies showed a small effect on SBP, but no effect on DBP, as mentioned previously (4). Similarly, a recent meta-analysis of 14 studies assessing the BP-lowering effect of the peptides isoleucine-prolineproline and valine-proline-proline exclusively in European subjects has shown a small decrease in SBP and DBP of 1.28 and 0.59 mmHg respectively (21). It cannot be ruled out that the use of BP-lowering medication, ACE/AT2 blockers in our study might have influenced the results; however, we do not find this likely as both dose and type of antihypertensive medication were kept constant during the study period.…”
Section: Discussionsupporting
confidence: 65%
“…Among these, lacto-tripeptides valine-proline-proline (VPP) and isoleucine-proline-proline (IPP) are resistant to GI digestion and can cross the mucosal barrier, resisting to digestion by serum peptidases (Foltz et al, 2008). VPP and IPP have been shown to reduce systolic blood pressure in hypertensive subjects (Boelsma and Kloek, 2010;Nakamura et al, 2011;Cicero et al, 2013), due to inhibition of angiotensin-converting enzyme (ACE), stimulation of vasodilator production, and modulation of sympathetic nervous activity (Usinger et al, 2010). In addition to antihypertensive effects, milk-derived peptidic fractions have been demonstrated to exert radical scavenging functionalities and prevent oxidative stresses associated with numerous degenerative chronic diseases, including cardiovascular ischemia, reperfusion, and atherosclerosis (Kudoh et al, 2001;Virtanen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Milk peptides which contain both caseins and whey proteins are a rich source of ACEI peptides. Val-Pro-Pro and Ile-Pro-Pro given at 5 to 60 mg/d have variable reductions in BP with an average decrease in pooled studies of about 1.28-4.8/0.59-2.2 mmHg [71,100,[104][105][106][107] . However several recent meta-analysis did not show significant reductions in BP in humans [106,108] .…”
Section: Proteinmentioning
confidence: 99%
“…Bovine casein-derived peptides and whey protein-derived peptides exhibit ACEI activity [102][103][104][105][106][107][108][109][110][111] . These components include B-caseins, B-lg fractions, B2-microglobulin and serum albumin [102][103][104]111] .…”
Section: Proteinmentioning
confidence: 99%